2023
DOI: 10.1021/acsomega.3c03929
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted and Microwave-Assisted Extraction of Phenolics and Terpenoids from Abelmoschus sagittifolius (Kurz) Merr Roots Using Natural Deep Eutectic Solvents

Tan Phat Vo,
Thuy Vy Pham,
Thi Ngoc Huyen Tran
et al.

Abstract: This research extracted phenolics and terpenoids from Abelmoschus sagittifolius (Kurz) Merr roots using natural deep eutectic solvent-based novel extraction techniques. Twelve natural deep eutectic solvents (NADESs) were produced for recovering phenolics and terpenoids. Citric acid/glucose and lactic acid/glucose, with a molar ratio of 2:1, were determined as the most appropriate NADESs for extracting phenolics and terpenoids, respectively. Afterward, the proper conditions for NADES-based ultrasonic-assisted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…ex D.Don [ 12 ], and Polygonatum sibiricum F.Delaroche [ 13 ], as well as different terpenoids from Abelmoschus sagittifolius Merr. [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ex D.Don [ 12 ], and Polygonatum sibiricum F.Delaroche [ 13 ], as well as different terpenoids from Abelmoschus sagittifolius Merr. [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the available literature data, NADESs were successfully implemented in the extraction of saponins [ 11 , 14 , 30 , 31 ]. Recently, we have reported the successful extraction of triterpene saponins from the roots of A. elata using a conventional maceration procedure, which involved using a broad selection of alternatively applied NADESs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there has been extensive research conducted on the use of NADESs in bioactive compounds extraction from various sources such as plants and food processing waste, including Abelmoschus sagittifolius (Kurz) Merr, blueberry leaves, coffee husk waste. Previous research conducted by Tan Phat Vo et al [5] focused on using NADES solvents to extract bioactive compounds from Bo Chinh ginseng. Marı ´a Santos-Martı ´n et al [6] used NADESs-based UAE to extract phenolic compounds from blueberry leaves.…”
Section: Introductionmentioning
confidence: 99%
“…glabra residue . Additionally, most active compounds of flavonoids, , terpenoids, and polyphenol , could be efficiently extracted from natural plants by DES.…”
Section: Introductionmentioning
confidence: 99%
“…34 Liu et al confirmed the possibility to apply DES for the Glabridin extraction from the G. glabra residue. 35 Additionally, most active compounds of flavonoids, 36,37 terpenoids, 38 and polyphenol 39,40 could be efficiently extracted from natural plants by DES. The method of macroporous resin adsorption has been extensively used in the purification of natural products.…”
Section: Introductionmentioning
confidence: 99%